PEMBERDAYAAN PENDIDIKAN TEKNIK BUSANA DI PERGURUAN TINGGI UNTUK PENGEMBANGAN INDUSTRI GARMEN DI PASAR GLOBAL - Noor Fitrihana (Jurnal Cakrawala Pendidikan, 2005)
Indonesian garment industries have been sluggishness. Since economic crisis incoming, Indonesian garment products loose ofthe competitiveness until now. In the last five years, perfonnance oftextile industry got decrease because many domestic probleII\'l. The problems are skills ofworkforce, out ofdate technology and poor of-fashion product inovation. Facing the global market ifnot good plan anticipate, gannent industries are cannot running growthand become sunset industry. To solve the problems, one of the ways is empowennent higher education institutions have links with them. That one is fashion design department in university. Market trend for the future is on "High Fashion and High Value Added Pnxluct Era". Facing the era and to improve perfonnance garment industries, fashion department in unive~ity must not only create fashion designer but also fashion engeener which capability to development and manufacturing fashion product to mass production. For this, fashion design department in university must to do effort developing the tri dhanna mission. First, in education mission, contents ofcurriculum are not only focus to create fashion designer but also to developing human resources with competence garment manufacturing. Second, improving research to developing fashion products with value added indesign, material, technology and how to aply these on variouse range of use not only ready we.ar for everyday in use. Thirth, for implementation misson to serve community can do with stylization traditional motif with modem touch to upgrading traditional fabric in global market.